2022
DOI: 10.1038/s41419-022-05451-y
|View full text |Cite
|
Sign up to set email alerts
|

m6A-modified circFNDC3B inhibits colorectal cancer stemness and metastasis via RNF41-dependent ASB6 degradation

Abstract: Colorectal cancer (CRC) is the third most frequently diagnosed cancer with unfavorable clinical outcomes worldwide. circFNDC3B plays as a tumor suppressor in CRC, however, the mechanism of circFNDC3B in CRC remains ambiguous. The stem-like properties of CRC cells were detected by the evaluation of stemness markers, sphere formation assay and flow cytometry. qRT-PCR, FISH, IHC, and western blotting assessed the expression and localization of circFNDC3B, RNF41, ASB6, and stemness markers in CRC. The metastatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
(73 reference statements)
1
12
0
Order By: Relevance
“…In this study, we found multiple circRNAs derived from the FNDC3B gene, and only hsa_circ_0001361 was overexpressed in OSCC, which might be due to the different biogenesis of these circRNAs. Several studies indicated that circFNDC3B (hsa_circ_0006156) could dramatically inhibit tumor progression including bladder cancer and colorectal cancer ( 36, 37 ). Furthermore, Yang and colleagues also found that high circFNDC3B (hsa_circ_0001361) expression in OSCC could repress cell ferroptosis (38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found multiple circRNAs derived from the FNDC3B gene, and only hsa_circ_0001361 was overexpressed in OSCC, which might be due to the different biogenesis of these circRNAs. Several studies indicated that circFNDC3B (hsa_circ_0006156) could dramatically inhibit tumor progression including bladder cancer and colorectal cancer ( 36, 37 ). Furthermore, Yang and colleagues also found that high circFNDC3B (hsa_circ_0001361) expression in OSCC could repress cell ferroptosis (38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to normal bowel tissues, YTHDC1 was downregulated in colon cancer (53). A recent study demonstrated that YTHDC1 accelerated the cytoplasmic translocation of m6A-modified circFNDC3B, thereby inhibiting CRC stemness and metastasis via RNF41-dependent ASB6 degradation (81).…”
Section: Effects Of Ythdcs On Crcmentioning
confidence: 96%
“…Therefore, novel therapeutic targets for the diagnosis and prognosis of CRC are urgently needed. CircFNDC3B was an originally identified promising biomarker that regulated CRC development ( 30 , 81 , 82 ).…”
Section: The Roles Of Circfndc3b In Cancersmentioning
confidence: 99%
“…Zeng et al. also found circFNDC3B was down-expressed in CRC tissues and low expression was related to poor OS ( 82 ). Experiments in vitro confirmed circFNDC3B could modulate CRC stemness and metastasis.…”
Section: The Roles Of Circfndc3b In Cancersmentioning
confidence: 99%